2019
DOI: 10.23736/s0022-4707.18.08920-x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, hydration and ergogenic aids strategies in ultraendurance mountain events

Abstract: The final version may contain major or minor changes.Subscription: Information about subscribing to Minerva Medica journals is online at: http://www.minervamedica.it/en/how-to-order-journals.php Reprints and permissions: For information about reprints and permissions send an email to:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…EXP was faster than NOV by 36 min, which was partially in agreement with previous studies (Till et al, 2016;Gordon et al, 2017). It was previously observed that fast marathon runners had more sport experience and weekly training volume than slow runners (Gordon et al, 2017), which was also in consonance with longer distance and running events as ultra-endurance mountain races (Belinchon-Demiguel and Clemente-Suarez, 2019). On the other hand, a study of the Australian marathons did not find any relationship between marathon race time and years of training; however, this result should be considered with caution since the sample size was relatively small (n = 19) (Till et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…EXP was faster than NOV by 36 min, which was partially in agreement with previous studies (Till et al, 2016;Gordon et al, 2017). It was previously observed that fast marathon runners had more sport experience and weekly training volume than slow runners (Gordon et al, 2017), which was also in consonance with longer distance and running events as ultra-endurance mountain races (Belinchon-Demiguel and Clemente-Suarez, 2019). On the other hand, a study of the Australian marathons did not find any relationship between marathon race time and years of training; however, this result should be considered with caution since the sample size was relatively small (n = 19) (Till et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…The lower muscular demands and the possibility of continuous food and hydration supplies, with lower assimilation problems (no vertical movements of centre of gravity) [18] could allow for a better control of pace, showing lower variations. In contrast, running limited the ingestion of both hydration and food supplies (vertical movements of centre of gravity, impact, movements) [19], fact that could modified the energy input necessary to maintain a steady pace during the race. Taking into account research in extreme environments, strenuous activities during various days could negatively affect cortical arousal, decreasing the information processing, hydration perception and rated of perceived exertion of the subjects [20].…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches found how in longer distance probes, athletes consumed significantly higher number of NSAIDs, being especially dangerous when is combined with a poor hydration strategy. Regarding caffeine intake, has been reported an increase in caffeine consumption in higher distance probe that could be explained since they consume more gels and isotonic drink with caffeine [21]. Regarding nutrition and hydration strategies in ultraendurance events previous researchers reported how higher performance athletes of longer distance presented higher water and nutritional ingestion than the lower ones [21].…”
Section: Introductionmentioning
confidence: 97%
“…Regarding caffeine intake, has been reported an increase in caffeine consumption in higher distance probe that could be explained since they consume more gels and isotonic drink with caffeine [21]. Regarding nutrition and hydration strategies in ultraendurance events previous researchers reported how higher performance athletes of longer distance presented higher water and nutritional ingestion than the lower ones [21]. Regarding the heart rate (HR) response, during a 21-h ultraendurance event athletes reached the 71% of maximum heart rate (HRmax) [22], and the heart rate variability (HRV) after an Ironman showed the increase in sympathetic modulation [23] and the increase in the rated of perceived exertion (RPE) [24].…”
Section: Introductionmentioning
confidence: 99%